A mitogenomic phylogeny of the Entomobryoidea (Collembola): A comparative perspective. (31st March 2021) - Godeiro, Nerivânia Nunes; Bellini, Bruno Cavalcante; Ding, Nifeng; Xu, Cong; Ding, Yinhuan; Zhang, Feng
Abstract: Mitogenomes have been widely used as markers to reconstruct phylogenies of various groups of arthropods, but specifically for Collembola they have not been useful to resolve the relationships between some families, such as Paronellidae and Entomobryidae. Here, we present a phylogenetic study integrating previously published data and 20 new mitogenomes, totalling 54 species of Entomobryoidea and two external groups. Eight of the nine subfamilies were included, with species from the most representative genera. The new mitogenomes were sequenced, assembled and annotated, resulting in sequences with a length of approximately 14, 000 bp. Phylogenetic analyses were conducted based on the 13 protein‐ and 2 rRNAs‐encoding genes of the 56 mitogenomes. Both maximum likelihood (with six different datasets/models) and Bayesian inference analyses were performed. Orchesellidae, Seirinae and Lepidocyrtinae were reaffirmed as monophyletic groups, while the phylogenetic relationships between Paronellidae and Entomobryidae remain confused. A complete resolution of the Entomobryoidea phylogeny will require a comprehensive genomic sampling of the most informative nuclear and mitochondrial markers to finally overcome traditional systematic problems.